2012
DOI: 10.1080/17533015.2012.665372
|View full text |Cite
|
Sign up to set email alerts
|

Managing evaluation: A community arts organisation's perspective

Abstract: Background Arts and health organisations must increasingly provide measurable evidence of impact to stakeholders, which can pose both logistical and ideological challenges. This paper examines the relationship between the ethos of an arts and health organisation with external demands for evaluation. Methods Research involved an ethnographic engagement where the first author worked closely with the organisation for a year. In addition to informal discussions, twenty semi-structured interviews were conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our participants indicated that much of their work fell outside of the traditional rubric of academic discourses of evaluation and measurement of impact, resulting in tensions in dealing with the expectations of fellow academics, funders, and journal reviewers. These expectations often include the demand for a particular type of evidence – that is observable in an objective manner and with associated measureable indicators of change to specific elements of health and wellbeing (Swan and Atkinson, 2012). This is a constraint, as much current evaluation of ABHR is based on subjective interpretation, often regarded as inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants indicated that much of their work fell outside of the traditional rubric of academic discourses of evaluation and measurement of impact, resulting in tensions in dealing with the expectations of fellow academics, funders, and journal reviewers. These expectations often include the demand for a particular type of evidence – that is observable in an objective manner and with associated measureable indicators of change to specific elements of health and wellbeing (Swan and Atkinson, 2012). This is a constraint, as much current evaluation of ABHR is based on subjective interpretation, often regarded as inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…This is also a feature of arts and health practice that is addressed to specific types of communities, or experiences of ill-health, where, as Parr describes, "a distinctive theme is a sense of shared illness experience" (2006,158). Agencies providing participatory arts and health activities constantly face the challenge of negotiating the demands of funders informed by the dominant model of a neoliberal subject whilst maintaining their own ethos of collective and relational care for well-being (Swan and Atkinson 2012). Without detracting from the importance of individual experience or silencing dissenting voices, such a collective approach questions the desirability of "personalized care" that separates the "ill" individual from the communities and spaces within which he or she lives.…”
Section: Medical Health and The Radical Potential Of The Medical Hummentioning
confidence: 99%
“…In these, mixing participants with diverse experiences is understood to contribute to societal cohesion and personal network-building (Milligan et al, 2016;Swan & Atkinson, 2012). In these, mixing participants with diverse experiences is understood to contribute to societal cohesion and personal network-building (Milligan et al, 2016;Swan & Atkinson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing interest in developing places to increase social connection; for example, Men's Sheds, community gardens and co‐working spaces. In these, mixing participants with diverse experiences is understood to contribute to societal cohesion and personal network‐building (Milligan et al., ; Swan & Atkinson, ). Aligned, social enterprises aim to enable disadvantaged individuals to develop social capability while also gaining work experience in commercial businesses (Barraket et al., ).…”
Section: Introductionmentioning
confidence: 99%